2021
DOI: 10.1021/acs.biomac.1c00565
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Collagen in Multilayers for Enzyme-Assisted Mineralization: A Promising Way to Direct Crystallization in Confinement

Abstract: The biogenic calcium phosphate (CaP) crystallization is a process that offers elegant materials design strategies to achieve bioactive and biomechanical challenges. Indeed, many biomimetic approaches have been developed for this process in order to produce mineralized structures with controlled crystallinity and shape. Herein, we propose an advanced biomimetic approach for the design of ordered hybrid mineralized nano-objects with highly anisotropic features. For this purpose, we explore the combination of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Moreover, by combining real-time monitoring and ex situ characterization techniques, we observed that the growth mechanism of the mineral was significantly impacted by the physicochemical conditions of the medium (pH and temperature). In another study, we embedded type I collagen within a multilayered film containing ALP in a way that mineralization was initiated in the vicinity of self-assembled collagen fibrils [ 134 ]. This led to an extensive formation of larger mineral particles, compared to the film without collagen, with higher surface coverage (see Figure 6 A,B insets).…”
Section: Enzymatic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, by combining real-time monitoring and ex situ characterization techniques, we observed that the growth mechanism of the mineral was significantly impacted by the physicochemical conditions of the medium (pH and temperature). In another study, we embedded type I collagen within a multilayered film containing ALP in a way that mineralization was initiated in the vicinity of self-assembled collagen fibrils [ 134 ]. This led to an extensive formation of larger mineral particles, compared to the film without collagen, with higher surface coverage (see Figure 6 A,B insets).…”
Section: Enzymatic Approachmentioning
confidence: 99%
“…This discrepancy suggests the existence of a different pathway when the mineralization is initiated by enzymes embedded in polyelectrolyte multilayers. Interestingly, the addition of type I collagen to the studied system induces noticeable effects [ 134 ]. For this purpose, collagen was embedded with ALP within the same multilayered film inside the nanopores.…”
Section: Enzymatic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 ] Further, the mineralization process is also guided by the interaction of enzymes and macromolecules, which control the morphology of mineral crystals and achieve orderly mineralization in various 3D networks. [ 15a,16 ] These bio‐macromolecular matrices are usually collagen and collagen‐mimicking polymers such as polysaccharides, alginate polyacrylamide, and oligo[poly(ethylene glycol) fumarate] hydrogel. [ 16–17 ] Due to the efficient catalytic activity of the enzymes, more uniform and orderly crystal growth has resulted in mineralizing fluid (MF), wherein CaGP is the main component.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15a,16 ] These bio‐macromolecular matrices are usually collagen and collagen‐mimicking polymers such as polysaccharides, alginate polyacrylamide, and oligo[poly(ethylene glycol) fumarate] hydrogel. [ 16–17 ] Due to the efficient catalytic activity of the enzymes, more uniform and orderly crystal growth has resulted in mineralizing fluid (MF), wherein CaGP is the main component. [ 16a ]…”
Section: Introductionmentioning
confidence: 99%